1988
DOI: 10.1128/jcm.26.10.2069-2076.1988
|View full text |Cite
|
Sign up to set email alerts
|

Determination of serum bactericidal activity against Escherichia coli by an automated photometric method

Abstract: The resistance of gram-negative bacteria to complement-mediated serum activity is supposedly an important virulence factor. However, the lack of standardization in the methods used to determine serum activity and the many definitions applied make the comparisons between studies very difficult. We developed a rapid photometric method that we compared with a classical killing one. Escherichia coli in the exponential phase of growth in brain heart infusion broth (final inoculum, 107 CFU/ml) at 35°C was added to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Blood was collected at approximately 1000 h each d into evacuated tubes without anticoagulant and allowed to clot for approximately 1 h. Serum was separated by centrifugation at 3,000 × g for 20 min at room temperature and placed in labeled tubes and frozen at −20°C until shipped to the laboratory for analysis of haptoglobin, serum bactericidal activity (SBA), and cortisol. Serum bactericidal activity against a live culture of bacteria was measured using methods similar to bactericidal activity of plasma (Crokaert et al, 1988;Moisá et al, 2018). Serum was incubated with Escherichia coli 8739 at a 1:8 ratio for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Blood was collected at approximately 1000 h each d into evacuated tubes without anticoagulant and allowed to clot for approximately 1 h. Serum was separated by centrifugation at 3,000 × g for 20 min at room temperature and placed in labeled tubes and frozen at −20°C until shipped to the laboratory for analysis of haptoglobin, serum bactericidal activity (SBA), and cortisol. Serum bactericidal activity against a live culture of bacteria was measured using methods similar to bactericidal activity of plasma (Crokaert et al, 1988;Moisá et al, 2018). Serum was incubated with Escherichia coli 8739 at a 1:8 ratio for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the higher adhesion and invasion levels observed here could be attributed to the fact that SV12 harbours a functional T6SS system. C. jejuni must be able to withstand the bile salts secreted into the intestinal tract and the bactericidal effects of the human and animal serum in order to cause infection [17]. In the present study, although both strains were susceptible to bile salts, SV12 showed increased survival compared to the C. jejuni 81–176 control strain.…”
Section: Discussionmentioning
confidence: 54%
“…To study the animal resistance on 28 th day of the experiment, the integral index of BSAA was determined using a culture of E. coli. E. coli (24 h culture) preparation, which consists of a dilution to 2×10 9 CFU in 1 mL of sterile saline solution (ZOMZ, Russia), followed by addition of 10 μL of the microbial suspension obtained to 4.5 mL of meat-peptone broth and incubation for 24 h (daily culture broth) [20].…”
Section: Blood Serum Antimicrobial Activity (Bsaa)mentioning
confidence: 99%